2018
DOI: 10.3390/rs10091488
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Impact of Land Cover Change on Surface Urban Heat Island through Google Earth Engine: Proposal of a Global Methodology, First Applications and Problems

Abstract: All over the world, the rapid urbanization process is challenging the sustainable development of our cities. In 2015, the United Nation highlighted in Goal 11 of the SDGs (Sustainable Development Goals) the importance to "Make cities inclusive, safe, resilient and sustainable". In order to monitor progress regarding SDG 11, there is a need for proper indicators, representing different aspects of city conditions, obviously including the Land Cover (LC) changes and the urban climate with its most distinct featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 41 publications
1
44
0
2
Order By: Relevance
“…The GEE greatly improves the processing efficiency when using substantial amounts of remote sensing data. In recent years, the GEE was used in land cover mapping [49][50][51][52][53][54][55][56][57][58], agricultural applications [59][60][61][62][63], disaster management, and earth sciences studies [64][65][66]. This remote sensing data processing cloud platform makes the rapid processing of Sentinel-2 images covering large areas possible.…”
mentioning
confidence: 99%
“…The GEE greatly improves the processing efficiency when using substantial amounts of remote sensing data. In recent years, the GEE was used in land cover mapping [49][50][51][52][53][54][55][56][57][58], agricultural applications [59][60][61][62][63], disaster management, and earth sciences studies [64][65][66]. This remote sensing data processing cloud platform makes the rapid processing of Sentinel-2 images covering large areas possible.…”
mentioning
confidence: 99%
“…We hypothesized that the use more imageries produces clearer output images to understand the LST patterns in the study area. Past studies have shown the aptness of this method to generate LST in different areas [39] [40]. All extracted images were georectified using the WGS84/UTM 44N projection system before further processing.…”
Section: Mountain Cities In Asia Have Been Developing Since the Colonmentioning
confidence: 99%
“…The use of more satellite images captured in multiple time point can potentially provide more specific information to understand the changing pattern of LST [4]. Still, it is not easy to analyze extensive earth observation data set due to spatial and temporal resolution [39] [40]. Thus, big data analysis platforms can be used as an alternative for conducting accurate result [39].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations